2015
DOI: 10.17576/jsm-2015-4406-01
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Characteristics of Palm-Based Polyurethane as a Lightweight Aggregate In Concrete Mix

Abstract: Research on the development of lightweight concrete (LWC) utilizing wastes and natural resources as lightweight aggregates (LWA) is increasingly gaining attention worldwide due to sustainable and environmental concerns. A new alternative is using palm kernel oil polyol (PKO-p)-based polyurethane (PU) as filler. Rigid PU is a block copolymer comprised of a monomeric . The property of PKO-p, PKO-p, Penyelidikan dalam membangunkan konkrit ringan (LWC) menggunakan bahan buangan dan sumber semula jadi sebagai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These foams are made up mostly of non-linear materials, and their characteristics are decided by thickness, internal air cavities, and the kind of crosslinking present in the structure of their molecules. Polyurethane foams are often classified as flexible, partially flexible/partially rigid or rigid concerning the chemical system, the stubbornness of the resin employed as a matrix, the mechanical responsiveness of the foams, and their cross-link identities [38].…”
Section: 2mentioning
confidence: 99%
“…These foams are made up mostly of non-linear materials, and their characteristics are decided by thickness, internal air cavities, and the kind of crosslinking present in the structure of their molecules. Polyurethane foams are often classified as flexible, partially flexible/partially rigid or rigid concerning the chemical system, the stubbornness of the resin employed as a matrix, the mechanical responsiveness of the foams, and their cross-link identities [38].…”
Section: 2mentioning
confidence: 99%
“…Recently, studies were directed toward investigating the potential of using bio-based polyurethane aggregate in concrete. Sari et al [ 30 ] studied the performance of using palm oil-based PU to partially replace aggregates from 0% to 3% to produce lightweight concrete. It was reported that as the aggregate replacement with palm-based PU increases, the compressive strength decreases and the thermal conductivity of concrete increases.…”
Section: Introductionmentioning
confidence: 99%
“…Several research works have been carried out to identify the parameters that govern the mechanical behavior of particulate composites. Generally, it has been found that the reinforcement effect increases with decreasing particle size and with the increasing of adhesion to the matrix [19]. Additionally, one observes a reduction in composite strength with increasing filler amount due to poor adhesion between the hydrophilic wood and the hydrophobic polymer [27].…”
Section: Introductionmentioning
confidence: 99%